High-Pressure Tuning of Magnon-Polarons in the Layered Antiferromagnet FePS3 - Pawbake, Amit; Pelini, Thomas; Delhomme, Alex; Romanin, Davide; Vaclavkova, Diana; Martinez, Gerard; Calandra, Matteo; Measson, Marie-Aude; Veis, Martin; Potemski, Marek; Orlita, Milan; Faugeras, Clement (ACS nano, 2022)
Magnetic layered materials have emerged recently as promising systems to introduce magnetism in structures based on two-dimensional (2D) materials and to investigate exotic magnetic ground states in the 2D limit. In this work, we apply high hydrostatic pressures up to P ≈ 8.7 GPa to the bulk layered antiferromagnet FePS3 to tune the collective lattice excitations (phonons) in resonance with magnetic excitations (magnons). Close to P = 4 GPa, the magnon-phonon resonance is achieved, and the strong coupling between these collective modes leads to the formation of new quasiparticles, the magnon-polarons, evidenced in our low-temperature Raman scattering experiments by a particular avoided crossing behavior between the phonon and the doubly degenerate antiferromagnetic magnon. At the pressure-induced magnon-phonon resonance, three distinct coupled modes emerge. As it is mainly defined by intralayer properties, we show that the energy of the magnon is nearly pressure-independent. We additionally apply high magnetic fields up to B = 30 T to fully identify and characterize the magnon excitations and to explore the different magnon-polaron regimes for which the phonon has an energy lower than, equal to, or higher than the magnon energy. The description of our experimental data requires introducing a phonon-phonon coupling not taken into account in actual calculations.